Pre-existing anti-drug antibodies in Fabry disease show less affinity for pegunigalsidase alfa - Malte Lenders; Solvey Pollmann; Melina Terlinden; Eva Brand (Molecular Therapy: Methods & Clinical Development, 2022)
We analyzed the cross-reactivity of anti-drug antibodies (ADAs) against agalsidase-alfa and -beta from 49 patients with Fabry disease (FD) against the novel PEGylated enzyme pegunigalsidase-alfa (PRX-102). The affinity of purified anti-AGAL antibodies from pooled patient sera was significantly lower for PRX-102 compared to agalsidase-alfa and -beta (both p < 0.05). Pull-down experiments revealed the presence of masked epitopes on PRX-102, possibly due to PEGylation. ADA titers in serum (μg/mL) and corresponding inhibitory capacities against agalsidase-alfa and -beta were measured in male patients with FD, showing strong correlations (r2 = 0.9978 and 0.4930, both p < 0.001). Affinities of ADAs of individual patients against PRX-102 (Kd: 3.55 ± 2.72 μmol) were significantly lower compared to agalsidase alfa (Kd: 1.99 ± 1.26 μmol) and -beta (Kd: 2.18 ± 1.51 μmol) (both p < 0.0001). Cross-ELISAs supported the presence of masked epitopes on PRX-102. Importantly, inhibition measurements also revealed a 30% reduction in inhibitory capacity of pre-existing ADAs towards PRX-102. Enzyme-uptake experiments in AGAL-deficient EA.hy926 cells demonstrated less effects of ADAs on cellular PRX-102 uptake compared with agalsidase beta. We conclude that due to the reduced affinity of pre-existing ADAs against agalsidase-alfa or -beta, ADA-affected patients might benefit from a therapy switch to PRX-102, which is currently evaluated in clinical trials.